Epistemologi Reformisme Islam Abad ke-19 di Mesir: Transformasi Historis Pemikiran Jamaluddin al-Afghani dan Muhammad Abduh - Abd. Bashir Fatmal; Jurrahmah AB. Yasin; Rahmawati; Syamzan Syukur (Batuthah: Jurnal Sejarah Padaban Islam, 2025)
In the 19 century, the Islamic world faced a great upheaval due to the expansion of Western colonialism and the epistemological crisis that struck its intellectual tradition. This condition gave rise to an urgent need for the reconstruction of Islamic thought that was able to respond to the challenges of modernity while at the same time maintaining Islamic identity. This article discusses the dynamics of Islamic reform in Egypt with its main focus on the epistemological synthesis formed from the teacher-student relationship between al-Afghani and Abduh, which aims to understand their ideas as a reference in creating Islamic thought in all aspects. The results of the research show that al-Afghani emphasized pan-Islamism and political resistance against Western hegemony, while Abduh focused on institutional reform, the rationalization of theology, and the modernization of Islamic education, particularly through Al-Azhar. Their collaboration through the publication of the journal Al-Urwah al-Wuthqa reflected the spirit of transnational reform that was able to reach various regions of the Islamic world. This article also highlights their contribution in shaping a reformist Islamic epistemology that integrates reason and revelation contextually. Their intellectual legacy not only dismantled the narrative of Islamic intellectual stagnation constructed by Orientalists, but also provided the foundation for the emergence of reform movements in South Asia and Southeast Asia. Thus, their ideas remain relevant in formulating Islam as a value system that is rational, ethical, and solution-oriented toward the modern problems of the Muslim community.